Mechanical and physical properties of coir-fibre boards - Apiwat Oranratnachai; Pama, Ricardo P.; Cook, David J.; The Government of Thailand (Bangkok : Asian Institute of Technology, 1976)
This research describes an investigation of the mechanical and physical properties of coirfibre board to be used as building material. The composite was tested for its mechanical properties in direct tension, axial compression, flexure and torsion. In addition, certain physical properties such as creep, shrinkage, water absorption, expansion, impact, permeability and combustibility, were also studied. The specimens were cast under a uniform casting pressure of 280 psi with three different fibre-cement ratios of 0.20, 0. 30 and 0.40 by weight. The investigation showed the feasibility of using coir-fibre board as building material for semi-permanent single $tory buildings. The experimental results obtained for the mechanical properties of the composite were compared with analytically predicted values based on the theoretical analysis presented by Bovornsombat. Good agreement exists between the experimental and the theoretical values.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Fiberboard; Building materials